Chrysostom and Generation Z: Resilience, Identiy, and Social Justice - Maddox, Tanita Tualla (Journal of youth and theology, 2024)
Generation Z (Gen Z) comprises current adolescent culture, bringing with them a generational worldview lens for topics such as: suffering, success, identify formation, and social justice. Gen Z values safety, has a heart for the outcasted, and is forming identity around successes and accomplishments. This article seeks to ground Gen Z with a piece of historical Christian faith and teaching, applying the fourth-century teachings of John Chrysostom to today’s Gen Z. Much like Chrysostom’s audience, Gen Z views suffering and hardship as punitive and to be avoided. Chrysostom’s teaching provides a fuller understanding of suffering, equipping his audience, and today’s Gen Z, with a mode for building resilience through thanksgiving. Chrysostom taught on the importance of charity, which allows Gen Z to engage their generational values for tolerance and acceptance in the Kingdom of God.